Pengaruh Ukuran Mata Jaring Bottom Gill Net Di Perairan Ohoi Namar Kabupaten Maluku Tenggara - Yuliana Anastasia Ngamel; Julianus Notanubun; Imanuel Musa Thenu; Benediktus Jeujanan (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Fish resources Utilization in Southeast Maluku waters uses fishing gear, one of them is the bottom gill net. This study aims to determine the composition of fish species caught with different bottom gill net mesh sizes and the effective mesh size. The method used in this study was an experimental method of fishing with different mesh sizes, namely 2.5 inches and 3 inches, as well as data analysis using the paired sample t test. There were five types of catch obtained at a mesh size of 2.5 inches, namely Bubara fish (Carangoides bajad) totaling 54 individuals (22.41%), Cockatoos (Skarus dimidiatus) 46 individuals (18.67%), Samandar (Siganus canaliculatus 35 individuals (14.52%), Sikuda (Lethrinus atkinsoni) 39 individuals (12.45%) and Jackfruit seeds (Parupeneus indikus) totaling 24 individuals (9.96%).The mesh size of 3 inches obtained the type of Cockatoo fish (Skarus dimidiatus) totaled 27 individuals (30.58%), Jackfruit seeds (Parupeneus indikus) 14 individuals (15.91%), Bubara (Carangoides bajad) 13 individuals (14.77%), Samandar (Siganus canaliculatus) 11 individuals (12 .50 %) and sand (Pentapodus nagascokiensis) 6 (6.62 %). The total weight of the catch in basic gill nets with different mesh sizes, namely a 2.5-inch mesh size, obtained a total catch weight of 49,731.44 grams with an average catch per operation of 4,521.04 grams, while for mezh size 3 inches of 21,615.51 grams with an average per operation of 1,965.05 grams. Based on the paired sample t-test, it showed a significant difference in the use of different mesh sizes on the total weight of the catch, where the total weight of the catches obtained in the 2.5-inch treatment was more than in the 3-inch treatment, which means that hypothesis H1 is accepted Hₒ rejected.